Atomistic dynamics of disconnection-mediated grain boundary plasticity: A case study of gold nanocrystals. (20th October 2022) - Zhu, Qi; Zhou, Haofei; Chen, Yingbin; Cao, Guang; Deng, Chuang; Zhang, Ze; Wang, Jiangwei
Highlights: Representative nucleation, propagation and interaction dynamics of grain boundary (GB) disconnections are visualized at the atomic scale. Sources and barriers of different disconnection nucleation dynamics in Σ11(113) GB are quantitatively compared. The universal interlinks and transitions among different disconnection dynamics are systematically elucidated, which dominate GB migration. A conceptual map of disconnection-mediated GB plasticity is established. Abstract: Grain boundary (GB) mediated deformation is a vital contributor to the plasticity of polycrystalline materials, where the disconnection model has become a widely recognized approach to depict the GB dynamics. However, experimental understanding of the atomistic disconnection dynamics remains scarce. In this case study of gold nanocrystals, atomistic disconnection dynamics governing the shear-coupled migration of flat GBs have been systematically investigated via in situ transmission electron microscopy nanomechanical testing supported by molecular dynamics simulations. Specifically, the site-dependent nucleation, shear-driven propagation, and diverse interactions associated with distinct GB disconnections are systematically elucidated and quantitatively compared. Moreover, the disconnection-mediated GB plasticity proves to prevail among different tilt and mixed GBs in gold. Eventually, a conceptual map of disconnection-mediated GB dynamics is established, which would furnish a unified understanding of GB plasticity in metallic materials.